Liquidity-saving mechanisms in collateral-based RTGS payment systems - Marius Jurgilas; Antoine Martin (Federal Reserve Bank of New York, 2010)
This paper studies banks' incentives for choosing the timing of their payment submissions in a collateral-based real-time gross settlement payment system and the way in which these incentives change with the introduction of a liquidity-saving mechanism (LSM). We show that an LSM allows banks to economize on collateral while also providing incentives to submit payments earlier. The reason is that, in our model, an LSM allows payments to be matched and offset, helping to settle payment cycles in which each bank must receive a payment that provides sufficient funds to allow the settlement of its own payment. In contrast to fee-based systems, for which Martin and McAndrews (2008a) show that introducing an LSM can lead to lower welfare, in our model welfare is always higher with an LSM in a collateral-based system.
Keywords: E42; E58; G21; 330; Liquidity-saving mechanism; intraday liquidity; payments; Bankgeschäft; Zahlungsverkehr; Bankenliquidität; Tagesgeldmarkt; Wohlfahrtsanalyse; Theorie